Selection of a forecasting method: Analytical hierarchy process approach - Bartusková, Terezie; Papalová, Marcela; Kresta, Aleš (Univerzita Pardubice, 2015)
Describing the future development of an organizational environment is crucial for the goal setting and strategy selection of an organization. In today's rapidly changing times it is not easy to predict how the internal and external surroundings of a company will change. Predicting the future development of an organization is not an easy task for managers but they must adopt it to succeed in market competition. Specifically managers must be familiar with forecasting methods which can help to predict the uncertain developments of the environment. There are many forecasting methods which are available, differing in their time requirements, financial demands, and in predictive accuracy. The goal of this paper is to characterize the most commonly used methods and to select the most appropriate one from the point of view of small and medium sized enterprises. These companies are usually limited in the finances that they can spend for strategy setting. They also do not employ a large number of experts, who can apply these methods. In this paper, a suitable forecasting method will be chosen by utilizing the Analytical Hierarchy Process (AHP) approach.
Keywords: forecasting; strategic management; strategic planning; forecasting methods; AHP method; C38; L10